Enamel decalcification during orthodontic treatment - Estioko, Leora Jean
Enamel declassification and its associated histologic damage has been continuing problem in the use of orthodontic banding techniques. From the results obtained from the different methods applied in the study, it could be inferred that there is really a significant difference between the varnishes and the polymeric adhesive materials. The adhesive materials which are etchant materials provided a more effective protection against enamel declassification. However, a study still should be conducted to determine the acceptability in orthodontic treatment.